Analisis Determinan Kekurangan Energi Kronik (KEK) pada Ibu Hamil di Wilayah Kerja Puskesmas Putri Ayu Kota Jambi - Khusnul Amalia Khamdiyah; Fajrina Hidayati; Usi Lanita; Ismi Nurwaqiah Ibnu; Silvia Mawarti Perdana (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a nutritional problem that has serious impacts on the health of both the mother and the fetus, such as increased risk of preterm birth, low birth weight, and labor complications. In Jambi City, CED cases have continued to rise year by year. This study aims to identify the determinants of CED among pregnant women in the working area of Putri Ayu Public Health Center, Jambi City. This study employed a quantitative approach with an analytical observational design using a cross-sectional method. The sample consisted of 82 pregnant women selected through purposive sampling. Data were collected using questionnaires and anthropometric measurements using MUAC. Data were analyzed using the Chi-Square test to examine the relationship between independent variables and the incidence of CED. The study found that the prevalence of Chronic Energy Deficiency (CED) among pregnant women was 28%. Statistical analysis revealed that infectious diseases (p=0.000), personal hygiene (p=0.009), environmental sanitation (p=0.037), education (p=0.004), occupation (p=0.000), and income (p=0.040) were significantly associated with CED in pregnant women. There is a significant relationship between infectious diseases, personal hygiene, environmental sanitation, education, occupation, and income with Chronic Energy Deficiency (CED) in pregnant women at Putri Ayu Public Health Center, Jambi City. It is expected that efforts to address chronic energy deficiency (CED) among pregnant women at Putri Ayu Public Health Center can be carried out through an integrated approach, including improvements in personal hygiene, environmental sanitation, prevention of infectious diseases, as well as enhancement of education, employment, and family income.